ESRA19-0315 Erector spinae plane block (ESPB) for non-intubated video-assisted thoracoscopic surgery (VATS). (30th August 2019) - Longo, F; Piliego, C; Costa, F
Abstract : Background and aims: Video-assisted thoracoscopic (VATS) wedge resection (WR) is a minimally invasive (non–rib-spreading), nonanatomic limited video-assisted resection of a lung portion. It is the appropriate procedure for small-sized lung nodules and is indicated for palliative cases in which heart and pulmonary function are poor. Erector spinae plane block (ESPB) provides effective anesthesia of the chest wall. We report the case of a 65-year-old woman with major comorbidities who underwent non-intubated thoracoscopic wedge resection under ESPB, because of her high risk for general anesthesia. Perioperative performance was good, and pain after surgery was well controlled. Methods: Written informed consent was obtained from the patient for use of the figure and case description. The block, performed with ultrasound guide and in-plane technique, was achieved injecting 20 ml of 0.375% ropivacaine deep to the fascial plane of the erector spinae muscle, from a caudal to cranial direction. The patient was also sedated with propofol and remifentanil in TCI infusion. No supraglottic device for airway management was used. Results: Perioperative performance was good, and pain after surgery was well controlled. The patient felt totally satisfied with the anesthesia technique. Pain was well controlled even the day after the surgery. Conclusions: Overall, non-intubated VATSWR under ESPB is a feasible, effective and safe procedure. It could be an alternative to general anesthesia or serratus anterior plane block.